1998
DOI: 10.1074/jbc.273.29.18292
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interactions of Plasminogen and Tissue and Vampire Bat Plasminogen Activators with Fibrinogen, Fibrin, and the Complex of d-Dimer Noncovalently Linked to Fragment E

Abstract: Vampire bat plasminogen activator (b-PA) causes less fibrinogen (Fg) consumption than tissue-type plasminogen activator (t-PA). Herein, we demonstrate that this occurs because the complex of D-dimer noncovalently linked to fragment E ((DD)E), the most abundant degradation product of cross-linked fibrin, as well as Fg, stimulate plasminogen (Pg) activation by t-PA more than b-PA. To explain these findings, we characterized the interactions of t-PA, b-PA, Lys-Pg, and Glu-Pg with Fg and (DD)E using right angle li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 42 publications
5
72
0
Order By: Relevance
“…Finally, the data show that the large decrease in the DSPA␣1 cofactor activity with the small FDPs is attributable to a large increase (ϳ43-fold) in the K A , indicating that the high affinity sites for DSPA␣1 disappear as the M w of the FDP approaches 0.48 ϫ 10 6 g/mol. This is consistent with the observations of Stewart et al (2), who showed that DSPA␣1 binds to intact fibrin with high affinity (K A ϭ 150 Ϯ 40 nM) but not to fragment DD/E (K A Ͼ Ͼ 3000 nM), the smallest possible FDP (M w ϭ 0.25 ϫ 10 6 g/mol).…”
Section: Isolation Of Fdps With M W Ranging From 048 ϫ 10supporting
confidence: 81%
See 2 more Smart Citations
“…Finally, the data show that the large decrease in the DSPA␣1 cofactor activity with the small FDPs is attributable to a large increase (ϳ43-fold) in the K A , indicating that the high affinity sites for DSPA␣1 disappear as the M w of the FDP approaches 0.48 ϫ 10 6 g/mol. This is consistent with the observations of Stewart et al (2), who showed that DSPA␣1 binds to intact fibrin with high affinity (K A ϭ 150 Ϯ 40 nM) but not to fragment DD/E (K A Ͼ Ͼ 3000 nM), the smallest possible FDP (M w ϭ 0.25 ϫ 10 6 g/mol).…”
Section: Isolation Of Fdps With M W Ranging From 048 ϫ 10supporting
confidence: 81%
“…Implications for the Fibrin Specificity of Plasminogen Activators-Recently, Stewart et al (2) demonstrated that plasminogen activation catalyzed by t-PA, but not DSPA␣1, is effectively stimulated by the fibrin degradation product DD/E. The authors speculated that this property may increase the fibrin selectivity of DSPA␣1, relative to t-PA, as the DD/E fragments released from the clot would continue to stimulate the t-PAcatalyzed but not the DSPA␣1-catalyzed plasminogen activation, and thus, the release of DD/E into the circulation would promote fibrinogenolysis in the presence of t-PA but not DSPA␣1.…”
Section: Comparison Of Cofactor Activities Of Fdps and Fibrin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Active site blocked t-PA was prepared by incubating the activator with a 5-fold molar excess of D-phenyl-prolyl-arginine chloromethyl ketone (PPACK; Calbiochem) as described previously (5,20). The molecular weight and extinction coefficient used for t-PA were 65,000 and ⑀ 1% 280 ϭ 20.0, respectively (4).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that (DD)E compromises the fibrin specificity of t-PA, because this soluble fragment is as potent as fibrin at stimulating Pg activation by t-PA (10, 11). Like fibrin, (DD)E binds t-PA and Pg with high affinity (5,10,12). In contrast to its predominantly finger-dependent interaction with fibrin,…”
mentioning
confidence: 99%